Pendidikan Multikultural Sebagai Jembatan Toleransi Antarumat Beragama - Gimin Edi Susanto (Jurnal Pelita Dharma, 2014)
The problem is taken from observations of this case is about the lack of tolerance among regions that occur at this time. Because of the narrow conception of religion, lack of understanding of religion, no matter the religious differences. Low laws aware and understand about multicultural education. This will have a negative effect for the life of the city in the community.The purpose of this paper is to find out and tell about the importance of multicultural education to promote tolerance among cities and the role of Buddhist conseption about multicultural education. so that it can be seen that how much influence to promote tolerance among regions.To achieve these objectives, the authors tried to find a variety of literature on mult. The authors collected data as observations pole. From obsevation it, the writer can draw conclusions.The results of this study showed the existence of conflicts in the society due to receive the difference in attitude and respect for one another and attitudes that can be covered by a multi-cultural education.Based on these observations, the authors conclude that multicultural education is very important to improve the city into peace and harmony. This multicultural education help to resolve conflicts about religion that happening now.Finally, the authors advise that the government and the community can work together to become a society that respects a determination by multicultural education. This is to create a society that is peaceful and harmonious.Keyword: Multicultural education, religious tolerance